“Isn’t it mad that we’re all psychologists and we can't talk about our feelings?”: A mixed-methods study exploring trainee clinical psychologists’ experience of (non)disclosure of psychological distress during training - Zamir, Aliya (2023)
Objective: Literature on trainee clinical psychologists’ mental health has highlighted elevated levels of mental health difficulties and/or psychological distress among trainees, and low levels of disclosure within the workplace. The current study aimed to explore 1) trainee experiences of disclosure and/or concealment of psychological distress during their training, 2) beliefs, assumptions or predictions related to disclosure and 3) responses to disclosure.